Eliciting patients' healthcare goals and concerns: Do questions influence responses?. (September 2022) - Scalia, Peter; van Deen, Welmoed K; Engel, Jaclyn A; Stevens, Gabrielle; Van Citters, Aricca D; Holthoff, Megan M; Johnson, Lisa C; Kennedy, Alice M; Reddy, Swathi B; Nelson, Eugene C; Elwyn, Glyn
There is increasing interest in asking patients questions before their visits to elicit goals and concerns, which is part of the move to support the concept of coproducing care. The phrasing and delivery of such questions differs across settings and is likely to influence responses. This report describes a study that (i) used a three-level model to categorize the goals and concerns elicited by two different pre-visit questions, and (ii) describes associations between responses elicited and the phrasing and delivery of the two questions. The questions were administered to patients with rheumatic disease, and patients with inflammatory bowel disease (IBD). Paper-based responses from 150 patients with rheumatic disease and 338 patients with IBD were analyzed (163 paper, 175 electronic). The goals and concerns elicited were primarily disease or symptom-specific. The specific goal and concern examples featured in one pre-visit question were more commonly reported in responses to that question, compared to the question without examples. Questions completed electronically before the visit were associated with longer responses than those completed on paper in the waiting room. In conclusion, how and when patients' goals and concerns are elicited appears to have an impact on responses and warrants further investigation.